2013
DOI: 10.1021/ja311721g
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Metallic Single-Walled Carbon Nanotube Networks to Semiconducting through Electrochemical Ornamentation

Abstract: Field-effect transistors (FETs) that incorporate single-walled carbon nanotube (SWNT) networks experience decreased on-off current ratios (I(on)/I(off)) due to the presence of metallic nanotubes. Herein, we describe a method to increase I(on)/I(off) without the need for either specialized SWNT growth methods or post growth processing steps to remove metallic nanotubes. SWNTs that were grown using conventional arc discharge methods were deposited from aqueous suspension. Then, the SWNTs in the network were deco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…[ 20 ] The light‐induced defect generation in carbon lattice by oxygen chemical adsorption either in the form of epoxy or ether groups [ 17,21 ] is a high‐potential method for local tuning of carbon nanomaterials properties. Moreover, several approaches for a nanotube local conversion by oxygen species grafting were suggested based on electrochemical doping [ 22 ] and plasmon‐induced selective oxidation [ 23 ] that poses the local presence of nanoparticles near the nanotube. Recently, the direct laser writing methods of two‐photon oxidation (TPO) of graphene and carbon nanotubes were demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…[ 20 ] The light‐induced defect generation in carbon lattice by oxygen chemical adsorption either in the form of epoxy or ether groups [ 17,21 ] is a high‐potential method for local tuning of carbon nanomaterials properties. Moreover, several approaches for a nanotube local conversion by oxygen species grafting were suggested based on electrochemical doping [ 22 ] and plasmon‐induced selective oxidation [ 23 ] that poses the local presence of nanoparticles near the nanotube. Recently, the direct laser writing methods of two‐photon oxidation (TPO) of graphene and carbon nanotubes were demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been made for this purpose using various methods such as solvent evaporation, 10,11 electric field, 12,13 magnetic field, 14,15 and flow field. [16][17][18] However, the SWNT superstructures achieved with these methods have been limited to simple ones such as oriented SWNTs on substrates 19,20 or nematic SWNTs in bulk. 21,22 Recently, amphiphilic molecules such as block copolymers, which exhibit rich phase behavior [23][24][25] and have been extensively used as templates for highly ordered hybrid nanostructured materials selectively incorporating nanoparticles, [26][27][28][29][30] have been proposed as an efficient route for fabricating SWNT superstructures with various architectures.…”
Section: Introductionmentioning
confidence: 99%
“…Current burning of the m-SWNTs in the active channel and post-channel-deposition treatment with chemicals which preferentially destroy m-SWNTs or convert them into s-SWNTs has been studied. [10][11][12] due to the fairly length of ~ 10 μm, the strips of 5 μm are formed to achieve mobility of 80 cm 2 /V-s and on/off ratio of 10 5 . [13] However, for generally shorter solution-processed SWNTs whose length is usually less than 5µm, the width of strips should go down to sub-micron dimension and the resultant short nanotubes may likely result in poor on-current and mobility.…”
Section: Introductionmentioning
confidence: 99%
“…10 shows the variation with channel length and strip width of the on/off ratio, on-current and mobility using DB71-sorted AP-SWNTs on HfO 2 /Si substrates.It is observed that with HfO 2 /Si wafer and DB71-sorted AP-SWNTs could achieve an on-current of 10.9±1.85×10 -3 μA/μm, and high mobility and on/off ratio of 21.9±8.72 cm 2 /V-s and 8.16x10 4 ±3.04×10 4 respectively. The combination of stripping and s-SWNT enrichment on HfO 2 dielectric substrates results in significantly improved performance over the unsorted and DB71-sorted AP-SWNTs on SiO 2 dielectric devices.…”
mentioning
confidence: 99%